2022
DOI: 10.1590/0103-8478cr20210112
|View full text |Cite
|
Sign up to set email alerts
|

Does financial literacy inevitably lead to access to finance services? Evidence from rural Ghana

Abstract: This study examined the determinants of financial literacy (FL) and its impact on access to financial services (AFS), using data collected from rural Ghana. A two-stage residual inclusion model is utilized to address the selection bias issue. The results showed that FL is affected by household heads’ age, gender, education, asset ownership, homeownership, and economics education. The results revealed that FL is significant and positively related to AFS, but its square shows an inverse relation with saving mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…Even so, widows (who lost their husbands) or single women know little about concepts relevant for day-to-day financial decisions (Bucher-Koenen et al, 2017). Previous studies on financial literacy in Ghana have focused on access to finance (Twumasi et al, 2021), retirement planning (Sarpong-Kumankoma, 2021), gender differences after retirement (Adam et al, 2018) and investment decision-making (Ayaa and Peprah, 2021). Sarpong-Kumankoma (2021) reports that only about 27% of adults in formal employment in Ghana are able to correctly answer three simple questions on inflation, interest compounding and risk diversification.…”
Section: Gender and Financial Literacy In Ghana 569mentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, widows (who lost their husbands) or single women know little about concepts relevant for day-to-day financial decisions (Bucher-Koenen et al, 2017). Previous studies on financial literacy in Ghana have focused on access to finance (Twumasi et al, 2021), retirement planning (Sarpong-Kumankoma, 2021), gender differences after retirement (Adam et al, 2018) and investment decision-making (Ayaa and Peprah, 2021). Sarpong-Kumankoma (2021) reports that only about 27% of adults in formal employment in Ghana are able to correctly answer three simple questions on inflation, interest compounding and risk diversification.…”
Section: Gender and Financial Literacy In Ghana 569mentioning
confidence: 99%
“…, 2017). Previous studies on financial literacy in Ghana have focused on access to finance (Twumasi et al. , 2021), retirement planning (Sarpong-Kumankoma, 2021), gender differences after retirement (Adam et al.…”
Section: Introductionmentioning
confidence: 99%
“…Access to IT is a determinant for AFS; thus, it is considered a channel to promote household access to financial services (AFS). Studies (e.g., Andoh et al, 2015;Ankrah Twumasi et al, 2022;Thomas and Spataro, 2018) have shown that many individuals are reframing from formal financial services because of poor financial knowledge and skills. However, the information needed to enhance financial education is now available on the radio, television programs, and the Internet.…”
Section: Access To Financial Services Plays a Mediating Influencementioning
confidence: 99%
“…First, access to IT is considered a channel for information acquisition, including financial skills and knowledge information, enabling individuals to overcome some barriers that prohibit them from using financial services and products. People's ability to participate in the financial market improves when they have access to knowledge about financial services (Ankrah Twumasi et al, 2022). Following the above discussion, the relevant question underlying the theoretical un-derpinning is how can IT vis-à-vis access to financial services improve farmers' income?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation